The new encyclopedia britannica in 30 volumes. Macropedia VOL.16 / William Benton - Benton, William (Estados Unidos de América: Encyclopedia Británica, Inc, 1977)
Rugby league, elements of design, ornament and imagery, uses of rugs and carpets, periods and centers of activity, rural society delineated rural peoples, problems of change, prehistory, the lands of rus, the Mongol period, Rurikid Muscovy, Romanov Muscovy, the reign of peter, the reign of Catherine II the great, the reign of Paul, the reigns of alexander I and Nicholas, from alexander II to Nicholas.
Ilustración, mapa, tabla
Col. Enc
Keywords: 1. ENCYCLOPEDIA 2. ENCYCLOPEDIA BRITANNICA-MACROPEDIA VOL 16 3. REFERENCE